Electrode material for flow battery and preparation method of electrode material

By etching the carbon felt and loading the polyhydroxy structure additive and transition metal oxide catalyst, the problem of insufficient activity and surface area of ​​graphite electrode material in the flow battery is solved, the battery performance and stability are improved, and high efficiency and Long-life battery application.

CN119133479APending Publication Date: 2024-12-13CHANGSHA HECHU NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411042085.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The electrochemical activity and specific surface area of ​​graphite electrode materials in existing flow batteries are insufficient, resulting in poor overall performance of the battery, and the inconsistency and efficiency attenuation of carbon felt caused by high-temperature activation treatment are difficult to solve.

Method used

Etching carbon felt is used as the electrode material, and the specific surface area is increased by surface etching, and the fiber is loaded with additives with polyhydroxy structures and transition metal oxide catalysts to improve battery performance and stability.

Benefits of technology

By increasing the specific surface area and uniformity of the carbon felt, the catalyst adhesion rate and battery cycle stability are improved, and high-efficiency battery performance improvement and cycle life extension are achieved, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133479A_ABST
    Figure CN119133479A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow batteries, and provides an electrode material for a flow battery and a preparation method of the electrode material. The electrode material takes an etched carbon felt as a substrate, the fiber surface of the etched carbon felt is of a porous structure, the pore diameter is 50-350nm, the pore depth is 0-110nm, the fiber surface of the etched carbon felt is loaded with an additive and a catalyst, the additive comprises an organic substance containing a polyhydroxy structure, and the catalyst comprises a catalyst and an organic substance containing a polyhydroxy structure. The catalyst comprises one or more of bismuth halide, bismuth oxide or tungsten oxide, and the loading capacity is 1%-15% of the weight of the etched carbon felt. The flow battery negative electrode material with high specific surface area and high electrocatalytic activity is prepared by adopting the graphite felt loaded metal oxide subjected to surface etching treatment, preferably bismuth oxide or tungsten trioxide and the like, and a necessary material basis is provided for development of high-performance VRFB.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of liquid flow batteries, and in particular to an electrode material for a liquid flow battery and a preparation method thereof. Background Art

[0002] Liquid flow battery is a new type of energy storage battery with a series of advantages such as flexible design, high efficiency, long cycle life, high safety and environmental friendliness. In recent years, the technology of all-vanadium liquid flow battery (VRFB) has developed rapidly, but VRFB still needs to overcome several technical obstacles to achieve large-scale commercial application. At present, graphite felt material has become the most widely used electrode material in VRFB due to its good conductivity, high stability and three-dimensional network structure. However, as an electrode material, the original graphite felt limits the comprehensive performance of the battery due to its poor electrochemical activity and small specific surface area.

[0003] At present, the flow battery electrodes on the market are mainly graphite felt electrodes represented by Liaoning Jingu carbon felt. The graphite felt is subjected to high-temperature activation treatment to prepare the required carbon felt. The battery efficiency of the carbon felt prepared by this method is limited, and the consistency of the carbon felt is poor and difficult to control. In addition, the high-temperature activation treatment will cause the efficiency of the battery to decay rapidly during the long-term cycle of the battery, and there are problems with stability.

[0004] Therefore, there is still a lack of a graphite felt electrode material for liquid flow batteries to solve the problem of poor overall battery performance due to the electrochemical activity and specific surface area of ​​the graphite electrode material. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the electrochemical activity and specific surface area of ​​the graphite electrode material lead to poor overall battery performance. In order to overcome the deficiencies and defects mentioned in the above background technology, an electrode material for a liquid flow battery and a preparation method thereof are provided.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] An electrode material for a liquid flow battery, the electrode material is based on etched carbon felt, the fiber surface of the etched carbon felt is a porous structure, the pore size is 50-350nm, and the pore depth is 0-110nm. The fiber surface of the etched carbon felt is loaded with additives and catalysts, the additives include organic substances containing polyhydroxy structures, the catalysts include one or more of bismuth halides, bismuth oxides or tungsten oxides, and the catalyst loading is 1%-15% of the weight of the etched carbon felt.

[0008] The present invention uses etched carbon felt as a substrate to increase the specific surface area of ​​the carbon felt, providing more attachment and activation sites for the catalyst, ensuring the uniformity of the carbon felt while improving battery performance; the additive on the surface of the carbon felt has a polyhydroxy structure and thus has a certain viscosity, which can fix the catalyst particles and further improve the attachment rate of the catalyst; during battery operation, after the catalyst is dissolved into the electrolyte, the stability of the battery during the cycle can be improved.

[0009] The catalyst includes, but is not limited to, bismuth halides, bismuth oxides, tungsten oxides and other transition metal oxides, which can promote the conversion of V 3+ and V 2+ The mutual conversion between them can reduce V 3+ and V 2+ Electrochemical polarization of the electrode couple improves energy efficiency.

[0010] Preferably, the additive includes monosaccharide and / or polysaccharide, more preferably monosaccharide or disaccharide. Small molecule sugars will not block the pores of the diaphragm, will not cause a significant change in the viscosity of the electrolyte, and can also avoid the hydrolysis of polysaccharides. Therefore, it is more advantageous to choose monosaccharide or disaccharide; the etching carbon felt component is graphite carbon felt, with a thickness of 2-4.5 mm and a density of 0.1-0.11 g / cm 3 , the porosity is 80%-95%.

[0011] Under the same technical concept, the present application also provides a method for preparing an electrode material for a flow battery, comprising the following steps:

[0012] (1) preparing an etching solution, placing the carbon felt in the etching solution for immersion, drying, calcining, and washing to obtain an etched carbon felt;

[0013] (2) preparing a loading solution, wherein the loading solution comprises an additive and a catalyst, spraying the loading solution uniformly onto the etched carbon felt, and drying the solution to obtain an electrode material for a liquid flow battery.

[0014] Etching carbon felt can increase the specific surface area of ​​carbon felt and provide more active sites for the catalyst.

[0015] Preferably, the etching solution comprises one or more of transition metal halides, metal oxides or alkalis, and the concentration of the etching solution is 0.05M-1M.

[0016] Preferably, the etching solution is a ferric chloride solution.

[0017] Preferably, the cleaning is carried out using concentrated hydrochloric acid.

[0018] Ferric chloride is used as the etchant. Compared with other etchants, ferric chloride is cheaper and more readily available. The reaction product is relatively simple and can be cleaned by the cleaning solution with less residue. During the high-temperature calcination process, the C on the carbon felt will convert Fe 3+ It is reduced to Fe and leaves holes on the carbon felt fibers. After calcination, the carbon felt is cleaned with concentrated hydrochloric acid, which dissolves excess ferric chloride, Fe and Fe oxides to obtain etched carbon felt.

[0019] Preferably, the calcination temperature is 300° C.-700° C., the calcination time is 30 min-12 h, and the soaking time is 5-20 min.

[0020] Preferably, the catalyst comprises one or more of bismuth halide, bismuth oxide or tungsten oxide, the additive comprises monosaccharide and / or disaccharide, the concentration of the additive solution is 1%-10%, the amount of the additive accounts for 1%-10% of the volume of the loading solution, and the amount of the loading solution relative to the area of ​​the etched carbon felt is 0.1-0.4 ml / cm 2 The amount of catalyst used is 1-4 mg / cm2 relative to the area of ​​the etched carbon felt. 2 , the solvent of the loading solution is a mixed solution of alcohol and water.

[0021] Preferably, the catalyst is bismuth oxide and / or tungsten trioxide solution, the 6p orbital of such catalyst is easy to form dp hybrid with the 3d orbital of vanadium, and has a good catalytic effect. The additive is lactose, which has a polyhydroxy structure, has a certain viscosity, and a small molecular weight, and is suitable as an additive for this application.

[0022] Preferably, the drying temperature is 70°C-90°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses a graphite felt subjected to surface etching to load a metal oxide, preferably bismuth oxide or tungsten trioxide, to prepare a liquid flow battery negative electrode material with high specific surface area and high electrocatalytic activity, providing the necessary material basis for the development of high-performance VRFB;

[0025] (2) Through low-energy consumption and simple process steps, the graphite felt with low activity is activated into an electrode material with excellent performance. The specific surface area of ​​the graphite felt is increased through an etching process, which provides more attachment and activation sites for the catalyst, ensuring the uniformity of the carbon felt while improving battery performance. Adding a sticky catalyst to the battery can fix the catalyst particles and improve the stability of the battery during the cycle without negatively affecting the battery performance, thereby achieving the purpose of improving battery efficiency, extending the battery cycle life, and reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a SEM image of Fe-etched carbon felt in Example 1;

[0028] Figure 2 is a SEM image of bismuth oxide loaded on Fe-etched carbon felt in Example 1;

[0029] Figure 3 This is the SEM image of ordinary carbon felt;

[0030] Figure 4 The electrode material used in the flow battery in Example 1 is used as the negative electrode, and the control group is tested by using carbon felt loaded with catalyst and additives as the negative electrode to obtain the current at 180 mA / cm 2 The cycle number diagram is carried out under the current density of ;

[0031] Figure 5 The graph of the number of cycles obtained by testing the electrode material for the flow battery used as the negative electrode in Example 1 and the carbon felt loaded catalyst and additive used as the negative electrode in the control group;

[0032] Figure 6 The ohmic impedance graph is obtained by testing the electrode material for the flow battery in Example 1 as the negative electrode and the carbon felt loaded with catalyst and additive as the negative electrode in the control group;

[0033] Figure 7 The results of the test at 180 mA / cm2 were obtained by using the etched carbon felt as the negative electrode in Example 1 and the control group using the carbon felt as the negative electrode. 2 Cyclic charge and discharge test diagram at a current density of ;

[0034] Figure 8 The results of the test at 180 mA / cm2 obtained by using ordinary carbon felt loaded with catalyst and additive as negative electrode in Example 2 and ordinary carbon felt as negative electrode in the control group were used as negative electrode. 2 Cyclic charge and discharge test diagram at a current density of ;

[0035] Fig. 9 This is a graph of the number of cycles obtained by testing the common carbon felt loaded with catalyst and additives as the negative electrode in Comparative Example 2 and the common carbon felt as the negative electrode in the control group;

[0036] Fig.10The ohmic impedance graph is obtained by testing the common carbon felt loaded with catalyst and additive as the negative electrode in Comparative Example 2 and the common carbon felt as the negative electrode in the control group;

[0037] Fig.11 is a SEM image of the carbon felt in Example 1; DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0039] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0041] Embodiment 1:

[0042] The present embodiment provides an electrode material for a flow battery. The electrode material is based on etched carbon felt. The fiber surface of the etched carbon felt is porous, with a pore size of 50-350nm and a pore depth of 0-110nm. The composition is graphite carbon felt, the thickness is 4-4.5mm, and the density is 0.1-0.11g / cm 3 The porosity is 80%-95%. The fiber surface of the etched carbon felt is loaded with additives and catalysts. The additive is lactose and the catalyst is bismuth oxide. The catalyst loading weight is 8.2% of the weight of the etched carbon felt and the additive loading weight is 0.59% of the weight of the etched carbon felt.

[0043] The above-mentioned method for preparing an electrode material for a flow battery comprises the following steps:

[0044] (1) Place the graphitized 4cm*4cm pre-oxidized felt into 100ml 0.3mol / L FeCl3 solution. After it is fully soaked, take out the carbon felt and put it into an 80℃ oven for drying. Then put the carbon felt into a muffle furnace and calcine it at 500℃ for 3h. Take it out and soak it in concentrated hydrochloric acid solution for 1h. After soaking, soak it in deionized water for 2h. Take out the carbon felt and put it into an 80℃ oven for drying to obtain the etched carbon felt.

[0045] (2) Add 32 mg of bismuth oxide powder and 0.1 ml of 5% lactose solution to 5 ml of 20% alcohol solution, ultrasonicate for 20 min, and evenly drop the mixture on the 4 cm*4 cm etched carbon felt treated as above, and dry the carbon felt in an oven at 80°C to obtain an electrode material for a liquid flow battery.

[0046] Figure 1 It is the SEM image of Fe-etched carbon felt in Example 1; a is a photo of etching time of 1h, b is a photo of etching time of 6h, and c is a photo of etching time of 3h. When the etching time is short, the carbon felt can also be effectively etched, but as the etching time increases, the number and depth of the etched holes gradually increase; the pictures show the etching effect of the carbon felt surface at different etching times, and the holes on the surface of each felt are uniform, indicating that the etching effect is excellent;

[0047] Fig.11 is a SEM image of the carbon felt in Example 1;

[0048] Figure 2 is a SEM image of bismuth oxide loaded on Fe-etched carbon felt in Example 1; a is an SEM image of 8.2% carbon felt in Example 1 at a magnification of 15,000, and c is an SEM image of 8.2% carbon felt in Example 1 at a magnification of 30,000. The images show that a large number of catalyst particles are attached to the surface of the carbon felt fiber, and the uniformity is relatively good.

[0049] Figure 3 This is a SEM image of ordinary carbon felt; this is an electron microscope image of carbon felt that has not been etched and loaded. There are no etched holes and catalyst particles on the surface, which is in contrast to the effect after etching and loading.

[0050] The electrode materials for the flow battery in step (2) above were used as the negative electrode and placed in a 3W all-vanadium flow battery at 180 mA / cm 2 The cyclic charge and discharge test was carried out at a current density of 2 mg / cm 2 Jingu carbon felt with bismuth oxide was used as negative electrode and put into 3W all-vanadium flow battery at 180mA / cm 2 The two batteries were tested under the same environment using the same device.

[0051] Figure 4 The electrode material used in the flow battery in Example 1 is used as the negative electrode, and the control group is tested by using carbon felt loaded with catalyst and additives as the negative electrode to obtain the current at 180 mA / cm 2 Cyclic charge and discharge test diagram at a current density of ;

[0052] Figure 5The graph of the number of cycles obtained by testing the electrode material for the flow battery used as the negative electrode in Example 1 and the carbon felt loaded catalyst and additive used as the negative electrode in the control group;

[0053] Figure 6 The graph of the number of cycles obtained by testing the electrode material for the flow battery used as the negative electrode in Example 1 and the carbon felt loaded catalyst and additive used as the negative electrode in the control group;

[0054] The test battery has an energy efficiency of 84.50%, a coulombic efficiency of 94.86%, a voltage efficiency of 89.08%, an ohmic impedance of 0.235Ω, an electrochemical reaction impedance of 3.722Ω, and a capacity retention rate of 95.57% after 100 cycles; the control battery has an energy efficiency of 82.78%, a coulombic efficiency of 94.64%, a voltage efficiency of 87.47%, an ohmic impedance of 0.234Ω, an electrochemical reaction impedance of 30.38Ω, and a capacity retention rate of 92.18% after 100 cycles.

[0055] Embodiment 2:

[0056] This embodiment provides an electrode material for a liquid flow battery, and the rest of the material is exactly the same as that of Embodiment 1, with the only difference being that the catalyst loading weight is 7.4% of the weight of the etched carbon felt.

[0057] Figure 2 It is the SEM picture of the Fe-etched carbon felt loaded with bismuth oxide in Example 1, wherein b is the electron microscope picture of the carbon felt with a loading amount of 7.4% in Example 2 at a magnification of 30,000. The picture shows that a large number of catalyst particles are attached to the surface of the carbon felt fibers with relatively good uniformity.

[0058] Comparative Example 1:

[0059] The carbon felt etched in Example 1 was used as the negative electrode and placed in a 3W all-vanadium redox flow battery at 180 mA / cm 2 The cyclic charge and discharge test was carried out at a current density of 180 mA / cm. This battery is an etched electrode battery. The carbon felt that has not been treated with other methods after graphitization was used as the negative electrode and placed in a 3W all-vanadium liquid flow battery. 2 The two batteries were tested under the same environment using the same device.

[0060] Figure 7 The results of the test on the negative electrode of the carbon felt after etching in Example 1 and the negative electrode of the control group using the ordinary carbon felt were 180 mA / cm 2 Cyclic charge and discharge test diagram at a current density of ;

[0061] like Figure 7As shown, the energy efficiency of the etched carbon felt electrode battery is 80.80%, the coulomb efficiency is 95.62%, and the voltage efficiency is 84.50%; the energy efficiency of the control battery is 75.12%, the coulomb efficiency is 95.56%, and the voltage efficiency is 78.61%.

[0062] Comparative Example 2:

[0063] This comparative example provides a method for preparing an electrode material for a flow battery, comprising the following steps:

[0064] (1) Prepare two pieces of 4 cm*4 cm Jingu carbon felt and label them as carbon felt a and carbon felt b respectively;

[0065] (2) Add 32 mg of bismuth oxide powder to 5 ml of 20% alcohol solution, which is called liquid a. Add 32 mg of bismuth oxide powder and 0.1 ml of 5% lactose solution to 5 ml of 20% alcohol solution, which is called liquid b. Ultrasonicate liquid a and liquid b for 20 min, then evenly drop the ultrasonicated liquid a and liquid b onto carbon felt a and carbon felt b, respectively, and dry the two pieces of carbon felt in an oven at 80°C to obtain electrode materials.

[0066] The untreated Jingu carbon felt was used as the negative electrode and placed in a 3W all-vanadium flow battery at 180 mA / cm 2 The three batteries were tested under the same environment using the same device.

[0067] Figure 8 The results of the test at 180 mA / cm2 obtained by using ordinary carbon felt loaded with catalyst and additive as negative electrode in Example 2 and ordinary carbon felt as negative electrode in the control group were used as negative electrode. 2 Cyclic charge and discharge test diagram at a current density of ;

[0068] Fig. 9 This is a graph of the number of cycles obtained by testing the common carbon felt loaded with catalyst and additives as the negative electrode in Comparative Example 2 and the common carbon felt as the negative electrode in the control group;

[0069] Fig.10 The ohmic impedance graph is obtained by testing the common carbon felt loaded with catalyst and additive as the negative electrode in Comparative Example 2 and the common carbon felt as the negative electrode in the control group;

[0070] In test a, the battery energy efficiency was 82.69%, the coulombic efficiency was 94.95%, the voltage efficiency was 87.09%, the ohmic impedance was 0.245Ω, the electrochemical reaction impedance was 7.554Ω, and the 100-cycle cycle capacity retention rate was 91.81%; in test b, the battery energy efficiency was 82.71%, the coulombic efficiency was 95.37%, the voltage efficiency was 86.73%, the ohmic impedance was 0.241Ω, the electrochemical impedance was 5.892Ω, and the 100-cycle cycle capacity retention rate was 94.39%; the control battery energy efficiency was 80.91%, the coulombic efficiency was 95.18%, the voltage efficiency was 85.01%, the ohmic impedance was 0.221Ω, the electrochemical reaction impedance was 21.6Ω, and the 100-cycle cycle capacity retention rate was 91.30%.

Claims

1. An electrode material for a flow battery, characterized in that: The electrode material is based on etched carbon felt, the fiber surface of the etched carbon felt is porous, the pore size is 50-350nm, and the pore depth is 0-110nm. The fiber surface of the etched carbon felt is loaded with additives and catalysts, the additives include organic substances containing polyhydroxy structures, the catalysts include one or more of bismuth halides, bismuth oxides or tungsten oxides, and the loading amount of the catalyst is 1%-15% of the weight of the etched carbon felt.

2. The electrode material according to claim 1, wherein the additive comprises monosaccharide and / or polysaccharide, and the etched carbon felt is graphite carbon felt with a thickness of 2-4.5 mm and a density of 0.1-0.11 g / cm 3 , the porosity is 80%-95%.

3. A method for preparing an electrode material for a flow battery, characterized in that: The following steps are involved: (1) preparing an etching solution, placing the carbon felt in the etching solution for immersion, drying, calcining, and washing to obtain an etched carbon felt; (2) preparing a loading solution, wherein the loading solution comprises an additive and a catalyst, spraying the loading solution uniformly onto the etched carbon felt, and drying the solution to obtain an electrode material for a liquid flow battery.

4. The preparation method according to claim 3, characterized in that: The etching solution includes one or more of transition metal halides, metal oxides or alkalis, and the concentration of the etching solution is 0.05M-1M.

5. The preparation method according to claim 4, characterized in that: The etching solution is a ferric chloride solution.

6. The preparation method according to claim 5, characterized in that: The cleaning adopts concentrated hydrochloric acid.

7. The preparation method according to claim 3, characterized in that: The calcination temperature is 300° C.-700° C., the calcination time is 30 min.-12 h. The soaking time is 5 min.-20 min.

8. The preparation method according to claim 3, characterized in that: The catalyst comprises one or more of bismuth halide, bismuth oxide or tungsten oxide, the additive comprises monosaccharide and / or disaccharide, the concentration of the additive solution is 1%-10%, the amount of the additive accounts for 1%-10% of the volume of the loading solution, and the amount of the loading solution is 0.1-0.4 ml / cm2 relative to the area of ​​the etched carbon felt. 2 The amount of catalyst used is 1-4 mg / cm2 relative to the area of ​​the etched carbon felt. 2 , the solvent of the loading solution is a mixed solution of alcohol and water.

9. The preparation method according to claim 8, characterized in that: The catalyst is bismuth oxide and / or tungsten trioxide solution, and the additive is lactose.

10. The preparation method according to claim 3, characterized in that: The drying temperature is 70°C-90°C.

Citation Information

Cited By

  • Preparation method of bismuth-based modified composite carbon felt electrode

    CN121983588A